Determination of thyroid hormones in dietary supplements using liquid chromatography–tandem mass spectrometry. Issue 3 (18th May 2021) - Pawar, Rahul S.; Sagi, Satyanarayanaraju; Leontyev, Dmitry
Abstract: More than 27 million Americans have some kind of thyroid disease. Numerous dietary supplements claiming to support healthy thyroid function and healthy metabolism and balance or promote weight loss are available for purchase in retail stores and on the internet. In the literature, there have been reports of adverse events associated with the consumption of thyroid hormone‐containing products. In this study, an LC‐MS/MS method was developed and validated for the analysis of thyroxine (T4), 3, 3′, 5‐triiodo‐l ‐thyronine (T3), 3, 3′, 5′‐triiodothyronine (rT3), 3, 5‐diiodothyronine (3, 5‐T2) and 3, 3′‐diiodothyronine (3, 3′‐T2) in dietary supplements. Sonication with methanol was used for the extraction of free hormones from nonglandular products. The tissue‐bound hormones from glandular thyroid products were extracted using a modified enzymatic digestion, in which the matrix was first extracted by sonication with methanol and then by enzymatic digestion with proteases. Both extraction methods provided acceptable recovery values between 78% and 116%. Fifty‐eight products making claims related to thyroid management were purchased over the internet from 2017–2018 and quantitatively analyzed for five hormones using the validated methods. Eleven out of 19 glandular products were found to contain quantifiable amounts of hormones. Maximum daily servings were also calculated for each product based on label information. The maximum amount of T4, T3, and rT3 per daily serving in the glandular products were up to 210, 32, and 7.6 μg/day, respectively. In the case of nonglandular products, which were labeled to contain plant extracts, vitamins, minerals, diiodo compounds, and so forth, the amounts of 3, 5‐T2 and 3, 3′‐T2 were up to 740 and 2700 μg/day, respectively. Abstract : An LC‐MS/MS method was developed and validated for the analysis of five thyroid hormones in dietary supplements. The method was used to analyze 58 products making claims related to thyroid management. ​